Analisis Stakeholder dalam Proses Implementasi Kebijakan Sultan Nikah Capingan Kota Surakarta - Yohanes Andika Setia Budi; Desiderius Priyo Sudibyo (Jurnal Mahasiswa Wacana Publik, 2022)
The purpose of this study is to analyze the role of stakeholders in the process of implementing the policy of Sultan Nikah Capingan. This research use descriptive qualitative approach. The sampling technique is purposive sampling. The data analysis technique used interactive analysis. The results of the study show that in the implementation process, the stakeholders have different roles. In the policy content variable, DPPKB acts as a key player but in other sub-variables it acts as a context center. Other stakeholders tend to act as subjects and crowds. Stakeholders who show consistency of high interest are KEMENAG, PHDI, WALUBI, KUA Jebres, PERMABUDHI. Furthermore, in the implementation context variable, the power, interest, and strategy sub- variables of DPPKB actors act as Key Players, while the other sub-variables are context center. Meanwhile, Stakeholders only act as subjects or crowds. Stakeholders who show consistency of high interest are KEMENAG, WALUBI, and KUA in each sub-district. In the end, the policy recommendation is that DPPKB, which plays a dominant role as a key player, must be able to improve the facilitators in providing services in accordance with policy decisions.